Estudo da influência da distorção da alma no momento crítico elástico de flambagem lateral com torção de vigas de Aço de alma não esbelta com seção I - Carla Cristiane Silva (2017)
This work is a study of the influence of the effect of web distortion in the value of the elastic critical moment of lateral torsional buckling of steel beams with doubly symmetric I-sections with non-slender web, including the impact that this effect may have on the analysis of standard procedures. The web distortion is a phenomenon where the steel web, during the buckling, suffers a lateral deflection, which causes reduction of the resistant moment. The study presents the comparison of critical moment values obtained by analytical procedures that do not consider the web distortion of the beam, some of them presented in the design standards, and the values, distortion included, obtained from Finite Element Methods analysis using the software ABAQUS. In order to reach a representative range of results, it is analyzed the behavior of simply supported beams with the effective length equal to the span, both flanges free to move laterally, with free warping and restrained twist in the both ends and restrained twist and warping in the both ends, subjected to uniform moment and transversal loads uniformly distributed and concentrated at midspan applied on the tensioned flange, at half height and on the compression flange of the cross section. It is also analyzed, under equal conditions, only eliminating the cases of uniform moment and end supports with restrained twist and warping, the behavior of beams with one flange fully or partially tensioned with continuous lateral restraint. The geometrical parameters evaluated, which influence the effect of the distortion, are mainly the length of the beams and the web slenderness, and also, the flange slenderness. It was concluded that the effect of the web distortion increases with the reduction of the length, with the increase of the web slenderness and with the decrease of the flange slenderness in beams with both free flanges. In many situations, shown in details in this work, disregarding this effect can lead to highly overestimated results, therefore, contrary to safety. In others situations, basically when the effective length is large, the web slenderness reduced and the flange slenderness not too small, this effect has little influence on the value of the critical moment and can even be neglected.